Analisis Kelayakan Video Animasi sebagai Media Pembelajaran pada Mata Pelajaran Kimia Kelas X SMA N 1 Batu - Thomas Jefri Sibagiang; Fajar Aditya Kusuma (Educational Note, 2026)
This study aims to analyze the feasibility of using animated videos as a learning medium in Chemistry for Grade X students at SMA Negeri 1 Batu. Effective learning media play a crucial role in enhancing students’ understanding of abstract Chemistry concepts, such as atomic structure, chemical bonding, and chemical reactions. Animated videos were chosen because they can present information visually and dynamically, which is expected to increase students’ interest in learning as well as their comprehension. This research employs a quantitative descriptive approach with an evaluative method. Data were collected through validation sheets completed by media experts and subject-matter experts, as well as student response questionnaires regarding the media used. The analysis results indicate that the developed animated videos meet feasibility criteria based on aspects of visual quality, clarity of narration, relevance of content to the curriculum, and ease of understanding. Validation by media experts obtained an average score of 91% (very feasible), while validation by subject-matter experts reached 88% (feasible). Meanwhile, student responses showed that 93% of them felt that the animated videos helped them understand difficult Chemistry material. These findings indicate that animated videos are feasible to be used as an alternative learning medium to support the teaching and learning process in the classroom. This study recommends the broader use of animation-based media for subjects that are abstract and conceptual.